Institutions, Program Implementation, and Macroeconomic Performance - Nsouli, Saleh (IMF Working Papers; Working Paper ;, 2004)
This paper assesses empirically the links among a country's institutions and political environment, its implementation of IMF-supported programs, and macroeconomic performance in a sample of 197 programs approved between 1992 and 2002. We find that a stronger institutional and political environment is associated with better macroeconomic outcomes, especially at longer time horizons. This direct beneficial effect of institutions on macroeconomic outcomes is in addition to their indirect effect through better program implementation. We also find that program implementation exerts an independent influence on macroeconomic outcomes, especially over shorter time horizons of up to two years. Better-implemented programs are associated with lower inflation and with initially weaker but ultimately stronger external and fiscal outcomes, but with a statistically insignificant impact on economic growth.